Catabolite Repression of Aox in Pichia pastoris Is Dependent on Hexose Transporter PpHxt1 and Pexophagy - Zhang, Ping (American Society for Microbiology (ASM), 2010)
In this work, the identification and characterization of two hexose transporter homologs in the methylotrophic yeast Pichia pastoris, P. pastoris Hxt1 (PpHxt1) and PpHxt2, are described. When expressed in a Saccharomyces cerevisiae hxt-null mutant strain that is unable to take up monosaccharides, either protein restored growth on glucose or fructose. Both PpHXT genes are transcriptionally regulated by glucose. Transcript levels of PpHXT1 are induced by high levels of glucose, whereas transcript levels of PpHXT2 are relatively lower and are fully induced by low levels of glucose. In addition, PpHxt2 plays an important role in glycolysis-dependent fermentative growth, since PpHxt2 is essential for growth on glucose or fructose when respiration is inhibited. Notably, we firstly found that the deletion of PpHXT1, but not PpHXT2, leads to the induced expression of the alcohol oxidase I gene (AOX1) in response to glucose or fructose. We also elucidated that a sharp dropping of the sugar-induced expression level of Aox at a later growth phase is caused mainly by pexophagy, a degradation pathway in methylotrophic yeast. The sugar-inducible AOX1 promoter in an Δhxt1 strain may be promising as a host for the expression of heterologous proteins. The functional analysis of these two hexose transporters is the first step in elucidating the mechanisms of sugar metabolism and catabolite repression in P. pastoris.